Financial integration and the wealth effect of exchange rate fluctuations - Cédric Tille (Federal Reserve Bank of New York, 2005)
A growing body of research emphasizes the direct impact of exchange rate movements on the value of U.S. foreign assets. Because a substantial amount of U.S. assets are denominated in foreign currencies, a depreciation of the dollar leads to large capital gains. First, we present a detailed decomposition of the U.S. balance sheet, which exhibits substantial leverage in terms of currencies and across asset categories. The United States holds 50 percent of GDP in foreign-currency assets and is long in FDI (foreign direct investment) and equity positions and short in debt and banking positions. Then, we incorporate these features of international financial integration in a simple general equilibrium model and analyze how they affect the international transmission of monetary shocks. We find that financial integration is a central component of the model, with the valuation gains from an exchange rate depreciation leading to a welfare effect that is at least as large as that stemming from nominal rigidities alone but possibly much larger. We characterize how interdependence is affected by the composition of the portfolio across asset categories and how structural features of the model interact with financial integration.
Keywords: F31; F41; F42; 330; foreign assets; valuation effect; exchange rate; interdependence; Auslandsvermögen; Wechselkurs; Vermögenseffekt; Transmissionsmechanismus; Allgemeines Gleichgewicht; USA